1988
DOI: 10.1177/002221948802100905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corrective Feedback on Word Accuracy and Reading Comprehension of Readers with Learning Disabilities

Abstract: This study examined reading comprehension and word recognition effects of corrective feedback during oral reading on the performance of readers with learning disabilities. In a repeated measures design, students with learning disabilities read under three treatment conditions: corrective feedback on every oral reading error, correction on meaning change errors only, and no feedback regardless of errors. Corrective feedback on oral reading errors had a significant positive effect on both word recognition accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 12 publications
3
18
1
1
Order By: Relevance
“…Pany and McCoy (1988) found that third-grade reading disabled children, who made a large number of errors during reading (10 to 15 percent errors), significantly improved their word recognition and their comprehension scores when given immediate feedback on every single error. When corrective feedback was provided after every error, the children made significantly fewer overall errors, significantly fewer meaning change errors during reading of the passage, significantly fewer errors on lists of error words presented on an immediate and delayed basis, and significantly fewer errors on passage comprehension questions.…”
mentioning
confidence: 94%
“…Pany and McCoy (1988) found that third-grade reading disabled children, who made a large number of errors during reading (10 to 15 percent errors), significantly improved their word recognition and their comprehension scores when given immediate feedback on every single error. When corrective feedback was provided after every error, the children made significantly fewer overall errors, significantly fewer meaning change errors during reading of the passage, significantly fewer errors on lists of error words presented on an immediate and delayed basis, and significantly fewer errors on passage comprehension questions.…”
mentioning
confidence: 94%
“…For example, for children with learning and reading disabilities, feedback increases the rates of correct responding (Perkins, 1988), the ability to interpret metaphors (Baechle & Lian, 1990), attributions about performance (Okolo, 1992), spelling accuracy (Kearney & Drabman, 1993), long division skills (Robinson, DePascale, & Roberts, 1989), and word recognition accuracy and reading comprehension (Huebusch & Lloyd, 1998;Pany & McCoy, 1988;Peverly & Wood, 2001;Schunck & Rice, 1993). Similarly, for children with mild to severe intellectual deficits, feedback has been shown to increase performance evaluations (Turner & Matherne, 1994), ability to read grocery words (Schuster, Morse, Griffen, & Worley, 1996), word recognition skills (Farmer, Kline, & Bryson, 1992), spelling ability (McDonnell, Thorson, Allen, & Mathot-Bruckner, 2000), and the number of correctly chained steps completed independently in daily living tasks (Mechling & Gast, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Feedback has been shown to be of great importance for the development of reading for both children with and without reading difficulties (e.g. McCoy and Pany, 1986;Pany and McCoy, 1988;Perkins, 1988;Spaai et al, 1991;Wise and Olson, 1998). Since a beginning or struggling reader who makes a reading mistake has great difficulties correcting himself or herself, feedback should be provided by someone else.…”
Section: Synthesis For Oral Feedbackmentioning
confidence: 99%